Participation and beliefs in popular religiosity : an empirical-theological exploration among Italian Catholics - Zaccaria, Francesco, 1978- (Empirical Studies in Theology, 2010)
Many academic disciplines have contributed to the study of popular religiosity, but the definition of this phenomenon and of its relation with official religion still remains a problematic topic. This book offers an empirical-theological investigation of popular religiosity by exploring among Italian Catholics the relation between popular religious participation (processions, pilgrimages, vows, et cetera) and religious beliefs. The investigated beliefs are beliefs about God, about human suffering in relation to God, about Jesus Christ, and about the church. The results indicate that popular religious participation influences some of these beliefs. This study contributes to an empirically based picture of a complementary relation between popular religiosity and official religion within the Catholic Church in Italy.